2015
DOI: 10.1103/physreve.91.032312
|View full text |Cite
|
Sign up to set email alerts
|

Thomson rings in a disk

Abstract: We discuss the basic principles of self-organization of a finite number of charged particles interacting via the 1/r Coulomb potential in disk geometry. The analysis is based on the cyclic symmetry and periodicity of the Coulomb interaction between particles located on several rings.As a result, a system of equations is derived, which allows us readily to determine with high accuracy the equilibrium configurations of a few hundreds charged particles. For n 200 we predict the formation of a hexagonal core and v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 24 publications
3
24
2
Order By: Relevance
“…The numerical solution of the system (15), (17) for the hard confinement provides a remarkable agreement with the MD calculations for equilibrium configurations up to n = 105, excluding a few cases (see Table I in Ref. 32). Our MD results agree with those of Ref.…”
Section: Molecular Dynamics and The Circular Modelsupporting
confidence: 70%
“…The numerical solution of the system (15), (17) for the hard confinement provides a remarkable agreement with the MD calculations for equilibrium configurations up to n = 105, excluding a few cases (see Table I in Ref. 32). Our MD results agree with those of Ref.…”
Section: Molecular Dynamics and The Circular Modelsupporting
confidence: 70%
“…In the Comment [2] by Amore it was found that the minimum energy configuration of N = 395 charges confined in disk and interacting via the Coulomb potential has a lower energy than the result of our molecular dynamics (MD) calculations [1]. Based only on this result Amore concluded that"...the formation of a hexagonal core and valence circular rings for the centered configurations, predicted by the model of Ref.…”
mentioning
confidence: 59%
“…Based only on this result Amore concluded that"...the formation of a hexagonal core and valence circular rings for the centered configurations, predicted by the model of Ref. [1], is not supported by numerical evidence and the configurations obtained with this model cannot be used as a guide for the numerical calculations, as claimed by the authors. In light of this findings, the validity of the model of Ref.…”
mentioning
confidence: 88%
See 2 more Smart Citations